Association of household wealth and education level with hypertension and diabetes among adults in Bangladesh: A propensity score-based analysis - Gupta, Rajat Das; Chakraborty, Promit Ananyo; Hossain, Md. Belal (Wiley Online Library, 2022)
This article was published in the European Journal of Tropical Medicine & International Health by Wiley Online Library [© 2021 John Wiley & Sons Ltd.] and the definite version is available at: https://doi.org/10.1111/tmi.13625 The Journal's website is at: https://onlinelibrary.wiley.com/doi/10.1111/tmi.13625